(untitled) (Revista Nacional de Odontología, 2019)
Introduction: Incorporating patient satisfaction as the main objective of health organizations is increasingly important, being a pillar of the dentist’s professional growth, it also results in a high impact on dental practice. The purpose of this work is to know the importance of patient satisfaction in dental care and update the factors that determine it. Methods: This study was carried out through a Scoping review, keywords were selected and the databases and search strategies were defined, as well as the inclusion and exclusion criteria, finally the data was extracted with the selected tool. Results: 31 articles from 19 countries were included, 90.32% consider the interpersonal factors of the dentist within the main variables, 51.61% corresponds to the quality of treatment, 48.38% the convenience, 45.16% to the relationships of the Staff, 41.93% to the pain management, 32.25% to the facilities and 29.03% to the costs. Conclusions: Dental care satisfaction is based on the factors that the patient perceives in the course of their consultation, the factors that developed in the decade of the 80’s are still valid, being the interpersonal relationships of the dentist the main one to consider and within this the communication, in addition to short waiting time, good pain management and finally a fair payment according to the benefit obtained.